2021
DOI: 10.1021/acsnano.1c07856
|View full text |Cite
|
Sign up to set email alerts
|

Immunotargeting of Nanocrystals by SpyCatcher Conjugation of Engineered Antibodies

Abstract: Inorganic nanocrystals such as quantum dots (QDs) and upconverting nanoparticles (UCNPs) are uniquely suited for quantitative live-cell imaging and are typically functionalized with ligands to study specific receptors or cellular targets. Antibodies (Ab) are among the most useful targeting reagents owing to their high affinities and specificities, but common nanocrystal labeling methods may orient Ab incorrectly, be reversible or denaturing, or lead to Ab-NP complexes too large for some applications. Here, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…Unlike other inorganic molecular marker such as quantum dots, these lanthanide-based UCNPs do not contain elements known to cause toxicity, and previous animal injections have been safely demonstrated in [38,47,55], opening the door to clinical translation. In addition to that, they are also able to be conjugated to antibodies enabling molecular targeting to cells, providing cellular level contrast and selectivity [51]. Table 1 includes a comparison of the two main types of time-resolved biomedical sensors: systems requiring optics [35,56] and their optics-free counterparts [47,57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other inorganic molecular marker such as quantum dots, these lanthanide-based UCNPs do not contain elements known to cause toxicity, and previous animal injections have been safely demonstrated in [38,47,55], opening the door to clinical translation. In addition to that, they are also able to be conjugated to antibodies enabling molecular targeting to cells, providing cellular level contrast and selectivity [51]. Table 1 includes a comparison of the two main types of time-resolved biomedical sensors: systems requiring optics [35,56] and their optics-free counterparts [47,57].…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis of Core/Shell aUCNPs β-phase NaEr 0.8 Yb 0.2 F 4 aUCNPs were synthesized with minor modifications of the previously described methodology [38,51]. The ErCl 3 •xH 2 O (0.32 mmol, 122 mg), YbCl 3 •6H 2 O (0.08 mmol, 31 mg), oleic acid (OA, 3.25 g), and 1-octadececene (ODE, 4 mL) precursors were added into a 50-mL three-neck flask with subsequent heating to 110 °C under vacuum.…”
Section: Nanoparticle Synthesismentioning
confidence: 99%
“…a) Reproduced with permission. [ 136 ] Copyright 2021, American Chemical Society. b) Reproduced with permission.…”
Section: Modification Strategies For Qdsmentioning
confidence: 99%
“…Pedroso et al reported a method for the preparation of Antibody-QDs using the binding ability between SpyCatcher and SpyTag. [136] The premise of this method is to attach SpyCatcher to the surface of QDs using covalent conjugation, as shown in Figure 5a. Succinimidyl ester-maleimide SM(PEG) 2 cross-linker introduces thiol-reactive groups to the surface of the nanoparticles, and then SM(PEG) 2 reacts with primary amines to form a stable maleimide intermediate, which can react with the single-Cys SpyCatcher proteins.…”
Section: Functionalizing With Biomoleculesmentioning
confidence: 99%
See 1 more Smart Citation